The diurnal cycle of rainfall in South Africa in the austral summer. (15th March 2012) - Rouault, Mathieu; Roy, Shouraseni Sen; Balling, Robert C.
Abstract The diurnal cycle of precipitation over South Africa during summer is analysed for the first time using hourly precipitation data from 103 stations for the period 1998–2007. Using harmonic analysis, we found the presence of a distinct diurnal cycle over most of South Africa regarding both the frequency and amount of precipitation events. The standardized amplitudes, indicative of the strength of the diurnal cycle across a region, are strongest over the interior and along the east coast of South Africa with up to 70% explained variance associated with the diurnal cycle. The time of maximum precipitation is late afternoon to early evening in the interior, and midnight to early morning along the Agulhas Current as well as inland in the northeast of the county. The proximity of the warm Agulhas Current plays a role in the diurnal cycle of rainfall at coastal stations. There is an early morning maximum in precipitation in the South West of the country with small amplitude in the diurnal cycle there. On average, the peak in precipitation amount leads the peak in frequencies of precipitation by 30 min to 1 h. Together with a high resolution climatological summer rain rate presented here and a detailed table for all stations, this study is a benchmark upon which model output or satellite estimate of the diurnal cycle can be compared within the region. Copyright © 2012 Royal Meteorological Society